2019
DOI: 10.1186/s40494-019-0273-y
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-mediated extraction of fatty acids in bilayer oil paint models: a comparative analysis of solvent application methods

Abstract: The impact of solvent exposure on oil paintings and the differences between solvent application methods are longstanding topics in cleaning studies. Solvent exposure is ideally kept to a minimum, because solvent swelling can lead to the extraction and displacement of reactive paint components. In particular, important concerns are fatty acids displacement resulting in metal soap formation and embrittlement of paint due to solvent exposure. In this study, the extraction of a saturated fatty acid (SFA) marker an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
0
20
1
Order By: Relevance
“…However, it is known that the exposure of oil paints to organic solvents for varnish removal, or to water for the removal of surface dirt, can affect the physicochemical properties of the paint in an undesired way [3][4][5] . For example, exposure to organic solvents can lead to embrittlement of paint 6,7 and to the extraction [8][9][10][11][12][13][14] and redistribution 15 of soluble paint components. An increased rate of formation of degradation products, such as crystalline metal soaps (complexes of metal ions and long-chain saturated fatty acids), has also been reported 15,16 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is known that the exposure of oil paints to organic solvents for varnish removal, or to water for the removal of surface dirt, can affect the physicochemical properties of the paint in an undesired way [3][4][5] . For example, exposure to organic solvents can lead to embrittlement of paint 6,7 and to the extraction [8][9][10][11][12][13][14] and redistribution 15 of soluble paint components. An increased rate of formation of degradation products, such as crystalline metal soaps (complexes of metal ions and long-chain saturated fatty acids), has also been reported 15,16 .…”
mentioning
confidence: 99%
“…For example, exposure to organic solvents can lead to embrittlement of paint 6,7 and to the extraction [8][9][10][11][12][13][14] and redistribution 15 of soluble paint components. An increased rate of formation of degradation products, such as crystalline metal soaps (complexes of metal ions and long-chain saturated fatty acids), has also been reported 15,16 . Although a considerable amount of progress has been made 3,4,[17][18][19] , the knowledge of the influence of solvent-based cleaning on fundamental chemical processes in oil paint does not currently allow for a reliable assessment of the risks involved in cleaning.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the interest on the potential role of the cleaning treatments as activating agents for degradation has become a field of active study. 30,[79][80][81] In this framework, unilateral NMR may be considered one of the most useful techniques to evaluate and monitor a cleaning treatment. With unilateral NMR, it is possible to measure the hydrogen depth profile, the relaxation times, and the self-diffusion coefficients of water and solvents within the paint layer in a nondestructive way.…”
Section: Unilateral Nmr Studies Of the Effects Of Water On Lead Whimentioning
confidence: 99%
“…New studies in metals and paintings cleaning are also reported: Baij et al [21] contributed to a better understanding of the impact of different methods of solvent application on oil paintings and highlighted important differences between these methods; Moretti et al [22] aimed at developing an efficient methodology for in situ assessing painting surfaces after the laser cleaning using optical coherence tomography (OCT) and reflection FT-IR spectroscopy complemented with laser induced fluorescence (LIF) spectroscopic measurements; Yiming et al [23] developed a new kind of eco-friendly gel based on PHB (poly-3-hydroxybutyrate), biodiesel (BD) and dimethyl carbonate (DMC) for the cleaning of wax-based coatings applied on indoor bronzes.…”
mentioning
confidence: 99%